Effects of Phosphorus and Zinc on the Neotropical Cladoceran Ceriodaphnia silvestrii by Dietary Routes - Rodgher, Suzelei [UNESP]; de Paulo, Fernanda Campos [UNESP]; Costa, Marina Grandchamp [UNESP]; Contador, Thais Miike [UNESP]; Rocha, Giseli Swerts; Espíndola, Evaldo Luiz Gaeta (Springer Nature, 2020)
Aquatic systems are seldom disturbed by a single stressor agent. Considering that nutrients and metals occur simultaneously in the environment, studies on the combined effects of these elements on the biota need to be carried out. The aim of this study was to evaluate the effect of the microalga Raphidocelis subcapitata exposed to different combinations of phosphorus (P) and zinc (Zn) on the neotropical cladoceran Ceriodaphnia silvestrii. The algae acclimated to P concentrations of 2.3 × 10−4 and 2.3 × 10−6 mol L−1 were exposed to concentrations of 0.10, 0.57, 1.13, and 2.27 × 10−6 mol Zn2+ L−1. The P acclimated algal cells showed different capacity to deal with external free Zn level, resulting in higher susceptibility to metal as P decreased in the test medium. Elevated cell metal values were observed in R. subcapitata acclimated to 2 × 10−6 mol P L−1 and exposed to Zn, as compared to the values found in the microalga exposed to 2 × 10−4 mol P L−1. A significant reduction in number of newborn produced by cladoceran was verified when the organism was fed alga containing 47 × 10−15 g Zn cell−1 (2 neonates per female) and 60 × 10−15 g Zn cell−1 (5 neonates per female). It was observed a decrease of 90% of C. silvestrii survival for the treatment with 47 × 10−15 and 60 × 10−15 g Zn cell−1. Algal cells acclimated to high and low concentrations of P were an important exposure route to Zn for C. silvestrii.
Keywords: Chronic toxicity; Metal; Microalgae; Nutrient; Zooplankton